Domestic wastewater treatment in parallel with methane production in a microbial electrolysis cell. (August 2016) - Moreno, R.; San-Martín, M.I.; Escapa, A.; Morán, A.
Abstract: Microbial electrolysis cells (MECs) have great potential as a technology for wastewater treatment in parallel to energy production. In this study we explore the feasibility of using a low-cost, membraneless MEC for domestic wastewater treatment and methane production in both batch and continuous modes. Low-strength wastewater can be successfully treated by means of an MEC, obtaining significant amounts of methane. The results also suggest that hydrogenotrophic methanogenesis reduce the incidence of homoacetogenic activity, thus improving the overall MEC performance. However, gas production rates are low and important aspects such as methane solubility in water still remain a challenge. Overall, MECs can offer competitive advantages not only for low-strength wastewater treatment but also as an aid to anaerobic methane production by improving the chemical oxygen demand (COD) removal and methane production rates. Highlights: A methane-producing MEC was fed with a low-strength domestic wastewater. Application of 1V reduced the time required to obtain total acetate removal by 50%. Hydrogenotrophic methanogens curbed hydrogen recycling and homoacetogenic activity. High HRTs improved MEC performance as well as gas-phase CH4 recovery.